1988
DOI: 10.1111/j.1365-2761.1988.tb00518.x
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastructural study of morphological changes in Atlantic salmon, Salmo salar L., during the development of cold water vibriosis

Abstract: The structural changes which occur in the heart, the lateral muscle and the large intestine during the development of cold water vibriosis in Atlantic salmon, Salmo salar L., have been studied by light and electron microscopy. The results strongly suggest a causative relationship between the presence of the fish pathogen. Vibrio salmonicida, and the observed pathological changes. Cell damage was invariably accompanied by the presence of the bacterium. A close relationship was found between the number of bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 11 publications
2
21
1
Order By: Relevance
“…Various virulence mechanisms, including protease activity and cytotoxicity, have been described for different Vibrio species (1,10,29,64). The tissue damage observed in fish suffering from CV may also be due to extracellular toxin activity (27,63). However, we examined the cytotoxicity in cell cultures according to protocols by Tunsjø et al (64), and we detected no cytopathogenic effects in any of six fish cell lines infected with LFI1238 or the ⌬litR mutant (unpublished results).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Various virulence mechanisms, including protease activity and cytotoxicity, have been described for different Vibrio species (1,10,29,64). The tissue damage observed in fish suffering from CV may also be due to extracellular toxin activity (27,63). However, we examined the cytotoxicity in cell cultures according to protocols by Tunsjø et al (64), and we detected no cytopathogenic effects in any of six fish cell lines infected with LFI1238 or the ⌬litR mutant (unpublished results).…”
Section: Discussionmentioning
confidence: 76%
“…However, it should be noted that Hjelmeland et al (25) also failed to identify any extracellular cytotoxins or proteolytic enzymes in their study. Additionally, in the intestines of moribund salmon with CV, where V. salmonicida dominates the microbial flora, an absence of tissue damage of the epithelium has been reported (63). This suggests that V. salmonicida probably relies on mechanisms other than extracellular toxins to attack the host and escape its immune system.…”
Section: Discussionmentioning
confidence: 99%
“…ordalii Ransom et al, 1984 Summer flounder, Paralichthys dentatus Soffientino et al, 1999 V. carchariae Brown shark, Carcharkinus plumbeus Bertone et al, 1996Grouper, Epinephelus coioides Lee et al, 2002 V. carchariae Brown shark, Carcharhinus plumbeus damsela Spiny dogfish, Squalus aczznthias Grimes et al, 1984Grimes et al, , 1985 Zorrilla et al, 2003 !7. marinus Atlantic salmon, Salrno salar Benediktsdottir et al, 1998 mimicus Red sea bream, Pagrus major Wu and Pan, 2000 V. parahaemolyticus Iberian toothcarp, Aphanius iberus Alcaide et aL, 1999 V. pelagius Turbot, Scophthalmus maximus Villamil et al, 2003 a, b V. salmonicida Atlantic salmon, Salmo salar Totland and Nylund, 1988 Turbot, Scophthalmus maMmus Angulo et al, 1994 V. spIendidus Salte et al, 1994;V. viscosus Atlantic salmon, Salmo salar Lunder et al, 1995;Bruno et al, 1998;Greger and Goodrich, 1999 V. vulnificus Grouper, Epinephelus sp.…”
Section: Vibriosis and Associated Vibrio Species In Cultured Fishmentioning
confidence: 99%
“…Light and electron microscopic studies showed necrotic tissues in the kidneys and bacteria in contact with injured endothelial cells. 8,9 Vaccines developed against coldwater vibriosis have been shown to give full protection against infection with V. salmonicida. 10 In spite of this, outbreaks of coldwater vibriosis occasionally occur in vaccinated Atlantic salmon.…”
mentioning
confidence: 99%